Palp-it: implementação do back-end para uma plataforma colaborativa de compartilhamento de gráficos táteis - LIMA, Hugo Henrique da Silva (2023)
Accessibility is a comprehensive term that encompasses several aspects related to the inclusion of people with disabilities. In this article, the importance of accessibility in special education is highlighted, with emphasis on adapting curriculum content to the needs of the target audience. The present study proposes a web platform called Palp-it, developed with the aim of creating an environment for sharing tactile graphics. For this, it uses a methodology that involves the modeling of systems and the application of technologies such as PHP, HTML and Angular in the development of the site. The results obtained were satisfactory, as we were able to establish an environment conducive to collaboration and sharing of teaching materials aimed to people with visual impairments. In addition, we identify and implement effective solutions to improve the responsiveness of the system.